1061 Is There Potential for Prevention of Emergency Open Hernia Repairs?. (19th August 2022) - Yang, P
Abstract: Aim: Emergency hernia repairs are associated with increased post-operative complications. We aim to compare symptoms and healthcare contacts prior to surgery in patients undergoing emergency hernia repair to those who underwent elective hernia repair. Method: Retrospective study of all patients with acutely strangulated/obstructed hernias between October 2019 and October 2021. Emergency repairs were compared with cohort of elective repairs carried out over the same study period. Results: 41 patients required emergency open hernia repairs. The median age was 79(range 44–91) years. 25 were inguinal hernias, 7 para-umbilical, 4 incisional, and 4 femoral. 14/41(35.4%) patients had healthcare consultation for hernia prior to acute presentation. Of these, 11(27.1%) were already awaiting elective surgery. 25/41(60.4%) patients were asymptomatic prior to acute presentation. 28/48(68.7%) patients were not aware of hernia diagnosis prior to emergency surgery. There was significantly higher presence of hernia symptoms, healthcare contact, and awareness of diagnosis, in the elective patients compared to the emergency group (P<0.05). There was significantly higher rate of in-patient stay and need for small bowel resection in emergency patients (P<0.001). We found significantly higher rates of wound infection, haematoma/seroma, and urinary retention in emergency repair patients compared to the elective group (P<0.01). Conclusion: Early diagnosis and hernia repair is required to prevent need for emergency surgery and reduce risks of post-operative complications. Improved patient education regarding early presentation would allow earlier detection and intervention. Lack of symptoms prior to incarceration, however, would hinder early presentation, and therefore potential for emergency surgery prevention remains limited.